Meaning of the glorious Koran/translated by Mohamed Marmaduke Pickthall (New York, 1954)
The Meaning of the Glorious Koran is instructive, because the translator, Marmaduke Pickthall, was an English convert to Islam. The Meaning of the Glorious Koran is how a Muslim wanted that message to be understood in the West.
Keywords: Religion